Comparative nutritional and toxicity analyses of beverages from date seed and barley powders as caffeine-free coffee alternatives - Mohd Jamil, N. A.; Al-Obaidi, J. R.; Mohd Saleh, N.; Jambari, N. N. (Universiti Putra Malaysia Press, 2022)
Coffee is one of the most preferred beverages due to its flavour and aroma, which is partially contributed by the presence of caffeine. However, there are many negative effects of caffeine on human health. Alternative products like date seed and barley beverage have become an interest to switch from caffeine to caffeine-free beverages. The present work thus aimed to evaluate the nutritional properties and toxicity of date seed and barley powders as compared to Arabica coffee powder. Samples were analysed for its caffeine content, antioxidant activity, and toxicity activity from boiled water extract, whereas the nutrition compositions and heavy metal contents were analysed based on respective extraction method performed. A mass spectral peak of caffeine was detected in the Arabica coffee but not in the date seed and barley powders. All three samples were shown to possess antioxidant activities with Arabica coffee yielding the highest. Arabica coffee, however, exhibited a moderate level of toxicity to human lung fibroblast (MRC-5) cell line with IC50 of 230 ± 40 µg/mL at the extract concentration. There was no inhibition on 50% MRC-5 cell viability showed by the date seed and barley powders up to 10 mg/mL extract concentration. The abundance of heavy metals detected in all samples was lower than the regulatory limits. Our findings therefore further supported the advantages of date seed and barley powders as alternatives to coffee beverage as both contained undetected amount of caffeine, low fat and high carbohydrate contents, and possessed good antioxidant activity with low potential health risks.